Effect of stage 0 sporulation mutations on subtilisin expression. - Ferrari, E (1986)
Subtilisin expression as a function of growth and sporulation was determined using a presubtilisin-beta-galactosidase gene fusion. An approximately 500-base-pair region upstream of the subtilisin gene and including the first eight codons of the presubtilisin protein was fused at the eighth codon of beta-galactosidase in the integrative vector pJF751. This gene fusion does not carry a signal sequence, and therefore its synthesis is uncoupled from maturation of presubtilisin. The fusion protein gene was integrated into a variety of recipient strains to test for the effect of various mutations on the initial rate of presubtilisin-beta-galactosidase synthesis. Among the spo0 mutations tested, the spo0A mutations showed a strong, 10-fold decrease in the rate of beta-galactosidase synthesis. This effect of the spo0A mutations was not evident when the presubtilisin-beta-galactosidase fusion was present on a multicopy plasmid. The sacU mutation, which was known to increase the extracellular level of levansucrase and proteases, was found to increase the synthesis of the presubtilisin-beta-galactosidase gene fusions 7-fold, and the hpr mutations were shown to increase the rate of presubtilisin-beta-galactosidase gene fusions 17-fold, indicating that these mutations influence either transcription or translation of the presubtilisin gene. However, the effect of these mutations was only observed in the stationary phase of growth, indicating they did not render synthesis constitutive. By using multicopy plasmids and an integrated gene fusion, it was shown that there is likely to be a titratable repressor controlling subtilisin synthesis.